NMDA receptor regulation of levodopa-induced behavior and changes in striatal G protein-coupled receptor kinase 6 and ß-arrestin-1 expression in parkinsonian rats - Wu N (Dove Medical Press, 2013)
Na Wu, Lu Song, Xinxin Yang, Weien Yuan, Zhenguo Liu Department of Neurology, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China Background: Parkinson’s disease is a neurodegenerative disorder caused by loss of dopaminergic neurons in the substantia nigra. The dopamine precursor, levodopa, remains the most effective and common treatment for this disorder. However, long-term administration of levodopa is known to induce characteristic dyskinesia, and molecular mechanisms underlying dyskinesia are poorly understood. Methods: In this study, we investigated the effect of 6-hydroxydopamine lesions in dopaminergic neurons and chronic treatment with levodopa on expression of G protein-coupled receptor kinase 6 and ß-arrestin-1, two key regulators of G protein-coupled receptors, in the rat striatum. Results: We found that a unilateral 6-hydroxydopamine lesion reduced expression of G protein-coupled receptor kinase 6 and ß-arrestin-1 protein in the lesioned striatum. Reduction of these two proteins persisted in 6-hydroxydopamine-lesioned rats on chronic levodopa treatment for 23 days. In addition, coadministration of the N-methyl-D-aspartate receptor antagonist, MK-801, and levodopa reversed the reduction of G protein-coupled receptor kinase 6 and ß-arrestin-1 in the striatum. MK-801 also attenuated levodopa-induced dyskinetic behavior. Conclusion: These data indicate that G protein-coupled receptor kinase 6 and ß-arrestin-1 in striatal neurons are sensitive to dopamine depletion and are downregulated in rats with Parkinson’s disease and in levodopa-treated rats with the disease. This downregulation seems to require activation of N-methyl-D-aspartate glutamate receptors. Keywords: dopamine, levodopa, levodopa-induced dyskinesias, G protein-coupled receptors, G protein-coupled receptor kinase dyskinesia